Case Report: A case of micropapillary thyroid carcinoma with level I cervical lymph node metastasis - Yang, Qi; Cheng, Wei; Liang, Qin-long; Yan, Li (Frontiers in Oncology, 2025)
Papillary thyroid carcinoma frequently metastasizes to cervical lymph nodes, particularly involving the central and lateral compartments. Metastasis to upper mediastinal lymph nodes is also not unusual. However, involvement of Level I cervical lymph nodes is rarely encountered. We report the case of a 25-year-old female who sought medical attention for enlarged lymph nodes in Level I of the neck and was subsequently diagnosed with papillary thyroid carcinoma based on biopsy results. Notably, ultrasound imaging revealed no detectable lesions in the thyroid gland.